Cybernetic times: Norbert Wiener, John Stroud, and the 'brain clock' hypothesis. (February 2020) - Schmidgen, Henning
In 1955, Norbert Wiener suggested a sociological model according to which all forms of culture ultimately depended on the temporal coordination of human activities, in particular their synchronization. The basis for Wiener's model was provided by his insights into the temporal structures of cerebral processes. This article reconstructs the historical context of Wiener's 'brain clock' hypothesis, largely via his dialogues with John W. Stroud and other scholars working at the intersection of neurophysiology, experimental psychology, and electrical engineering. Since the 19th century, physiologists and psychologists have been conducting experimental investigations into the relation between time and the brain. Using innovative instruments and technologies, Stroud rehearsed these experiments, in part without paying any attention at all to the experimental traditions involved. Against this background, this article argues that the novelty of Wiener's model relies largely on his productive rephrasing of physiological and psychological findings that had been established long before the Second World War.